Stereoselective Arene‐Forming Aldol Condensation: Synthesis of Configurationally Stable Oligo‐1, 2‐naphthylenes. Issue 8 (21st January 2016) - Lotter, Dominik; Neuburger, Markus; Rickhaus, Michel; Häussinger, Daniel; Sparr, Christof
Abstract: Structurally well‐defined oligomers are fundamental for the functionality of natural molecular systems and key for the design of synthetic counterparts. Herein, we describe a strategy for the efficient synthesis of individual stereoisomers of 1, 2‐naphthylene oligomers by iterative building block additions and consecutive stereoselective arene‐forming aldol condensation reactions. The catalyst‐controlled atropoenantioselective and the substrate‐controlled atropodiastereoselective aldol condensation reaction provide structurally distinct ter‐ and quaternaphthalene stereoisomers, which represent configurationally stable analogues of otherwise stereodynamic, helically shaped ortho‐phenylenes. Abstract : Keep in good shape : The stereoisomers of configurationally stable oligo‐1, 2‐naphthylenes were obtained by repeated building block addition and stereoselective arene‐forming aldol condensations. The helix sense of the secondary structure was induced with 95:5 enantiocontrol by a natural amino acid as catalyst, and quaternaphthalene diastereoisomers featuring two chirality axes were accessible. CRU: constitutional repeating unit; EG: end group.